Square roots in square brackets

y = 1 + 2 + 3 + + x 2 1 \large y= \left\lfloor \sqrt { 1 } \right\rfloor +\left\lfloor \sqrt { 2 } \right\rfloor +\left\lfloor \sqrt { 3 } \right\rfloor +\dots +\left\lfloor \sqrt { { x }^{ 2 }-1 } \right\rfloor

Let x x and y y be a pair of prime numbers.

If pairs { x 1 , y 1 } , { x 2 , y 2 } , { x 3 , y 3 } { x n , y n } \left\{ { x }_{ 1 },{ y }_{ 1 } \right\} ,\left\{ { x }_{ 2 },{ y }_{ 2 } \right\} ,\left\{ { x }_{ 3 },{ y }_{ 3 } \right\} \dots \left\{ { x }_{ n },{ y }_{ n } \right\} are all of the solutions to the equation above, find the value of i = 1 n x i y i \displaystyle \sum _{ i=1 }^{ n }{ { x }_{ i }{ y }_{ i } } .


The answer is 45.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Patrick Corn
Jul 29, 2015

There are 2 n + 1 2n+1 terms equal to n n for each n n , because there are 2 n + 1 2n+1 integers in [ n 2 , ( n + 1 ) 2 ) [n^2,(n+1)^2) . So y = n = 1 x 1 n ( 2 n + 1 ) = ( x 1 ) x ( 2 x 1 ) 3 + x ( x 1 ) 2 = x ( x 1 ) ( 4 x + 1 ) 6 . y= \sum_{n=1}^{x-1} n(2n+1) = \frac{(x-1)x(2x-1)}3 + \frac{x(x-1)}2 = \frac{x(x-1)(4x+1)}6.
Clearly ( 2 , 3 ) (2,3) and ( 3 , 13 ) (3,13) are solutions, so we need only show that for x 4 x \ge 4 , y y cannot be prime.

Well, at least one of the three terms in product in the numerator is even, and at least one is divisible by 3. Suppose x 4 x \ge 4 . Call the terms f 1 , f 2 , f 3 f_1, f_2, f_3 . Note that all the f i f_i are at least 3 3 .

If 2 f 1 2|f_1 and 3 f 1 3|f_1 , then we can write y = ( f 1 / 6 ) f 2 f 3 y = (f_1/6)f_2f_3 as a product of three numbers, at least two of which ( f 2 f_2 and f 3 f_3 ) are strictly greater than 1 1 , so it can't be prime.

If 2 f 1 2|f_1 and 3 f 2 3|f_2 , then we can still write y y in that way, because we can write y = ( f 1 / 2 ) ( f 2 / 3 ) f 3 y = (f_1/2)(f_2/3)f_3 and both f 1 / 2 f_1/2 and f 3 f_3 are strictly greater than 1 1 .

Those are the only two cases (after we reorder the terms appropriately), so y y cannot be prime for x 4 x \ge 4 . So the answer is 2 3 + 3 13 = 45 2 \cdot 3 + 3 \cdot 13 = \fbox{45} .

wow this is so easy to understand! :) thank u

이채 린 - 5 years, 10 months ago

Log in to reply

Beautiful solution. I just followed my intuition and blasted 45 = (2 3) + (3 13) in as soon as I discovered that x=5 implies that y is not prime. Nice proof.

Chester Gan - 5 years, 10 months ago
Andrea Palma
Aug 9, 2015

Note that 1 + + x 2 1 = \left\lfloor \sqrt{1} \right\rfloor + \cdots + \left\lfloor \sqrt{x^2 -1} \right\rfloor = 1 + 1 + 1 + 2 + 2 + 2 + 2 + 2 + + ( x 1 ) + ( x 1 ) + + ( x 1 ) 2 x + 1 times 1 + 1 + 1 + 2 +2 +2 +2+2 + \cdots + \overbrace{(x-1) + (x-1) + \cdots + (x-1)}^{2x+1 \mbox{ times}}

hence the sum defining y y can be easily written as

y = i = 1 x 1 ( 2 i + 1 ) i = i = 1 x 1 2 i 2 + i = y = \sum_{i=1}^{x-1} (2i+1)\cdot i= \sum_{i=1}^{x-1} 2i^2 + i = 2 i = 1 x 1 i 2 + i = 1 x 1 i = ( x 1 ) x ( 2 x 1 ) 3 + ( x 1 ) x 2 2\sum_{i=1}^{x-1} i^2 + \sum_{i=1}^{x-1}i = \dfrac{(x-1)x(2x-1)}{3} + \dfrac{(x-1)x}{2}

that leads to

6 y = x ( x 1 ) ( 4 x + 1 ) 6y = x(x-1)(4x+1)

Now x x is prime, and it divides 6 y 6y so either x x divides 6 6 , or x x divides y y .

In the first case x x can be 2 2 or 3 3 . Both values, put in the equation, give a prime number for y y .

Namely we have x = 2 y = 3 x=2\ \Rightarrow y = 3 and x = 3 y = 13 x = 3 \Rightarrow y= 13 .

In the second case x x divides y y . But y y is prime and this means x = y x = y .

Putting x = y x = y in the equation we have ( x 1 ) ( 4 x + 1 ) = 6 (x-1)(4x+1) = 6 that has no integer solutions.

So the only pair of prime solutions are ( 2 ; 3 ) (2;3) and ( 3 ; 13 ) (3;13) and the answer is 45 45 .

Terms from floor(x-1) up to floor (sqrt(x^2 -1 ) all have value (x-1)

Such (2x-1) terms are there.

So the expression of y is sum of terms (x-1)(2x-1) for all prime values of x.

For x=2, y=3

For x=3, y=13

All higher values of y are found composite.

So answer is 2x3+3x13 = 45

Someone please provide complete analytical solution.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...